The last Olympian : the graphic novel - Venditti, Robert; Collar, Orpheus; e; Riordan, Rick. (Los Angeles : Disney-Hyperion, 2019)
The long-awaited prophecy surrounding Percy Jackson's sixteenth birthday unfolds as he leads an army of young demigods to stop Kronos in his advance on New York City, while the Olympians struggle to contain the rampaging monster, Typhon.
3.6
5-8
GN360L
Keywords: Mythology, Greek -- Juvenile fiction; Fate and fatalism -- Juvenile fiction; Monsters -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Titans (Mythology) -- Juvenile fiction; Mythology, Greek -- Comic books, strips, etc. -- Fiction; Fate and fatalism -- Comic books, strips, etc. -- Fiction; Monsters -- Comic books, strips, etc. -- Fiction; Animals, Mythical -- Comic books, strips, etc. -- Fiction; Titans (Mythology) -- Comic books, strips, etc. -- Fiction; Fantasy comics; Graphic novel adaptations; Graphic novels; Graphic novels